2023
DOI: 10.5194/bg-20-687-2023
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous oxide (N2O) synthesis by the freshwater cyanobacterium Microcystis aeruginosa

Abstract: Abstract. Pure cultures of the freshwater cyanobacterium Microcystis aeruginosa synthesized nitrous oxide (N2O) when supplied with nitrite (NO2-) in darkness (198.9 nmol g-DW−1 h−1 after 24 h) and illumination (163.1 nmol g-DW−1 h−1 after 24 h), whereas N2O production was negligible in abiotic controls supplied with NO2- and in cultures deprived of exogenous nitrogen. N2O production was also positively correlated to the initial NO2- and M. aeruginosa concentrations but was low to negligible when nitrate (NO3-)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The higher concentrations imply that an N 2 O source was present on the lake surface, as some types of cyanobacteria and green algae produce N 2 O (Weathers, 1984;Fabisik et al, 2023).…”
Section: Study Limitationsmentioning
confidence: 99%
“…The higher concentrations imply that an N 2 O source was present on the lake surface, as some types of cyanobacteria and green algae produce N 2 O (Weathers, 1984;Fabisik et al, 2023).…”
Section: Study Limitationsmentioning
confidence: 99%
“…The role of this enzyme has not been described yet, but its presence suggests another potential pathway for NO synthesis from NO 2 − in the mitochondria. Bellido-Pedraza et al [27] estimated that nearly one third of the 100 photosynthetic microorganisms described in genomic databases contain at least one of the proteins involved in N 2 O synthesis in Chlamydomonas (NirK, CYP55, FLVs, and HCP), including the widely distributed and dominant cyanobacterium in freshwater ecosystems Microcystis aeruginosa [18]. There is, therefore, clear evidence for the existence of several broadly distributed N 2 O synthesis pathways in microalgae.…”
Section: N 2 O Emissions From Microalgae Ecosystemsmentioning
confidence: 99%
“…Challenging this view, eutrophic aquatic environments are characterized by the abundance of microalgae whose growth is not necessarily linked (or linearly correlated) to the N inputs received and whose ability to produce N 2 O has now been clearly demonstrated [12][13][14][15][16][17]. Microalgae species from the Bacillariophyta, Chlorophyta, and Cyanobacteria have indeed been shown to synthesize N 2 O in the laboratory [13,18] and significant N 2 O emissions have been reported during microalgae cultivation outdoors [12,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…This respiration in turn is determined by remineralization of algal material from the upstream river that is transported to and respired within the port region (Schroeder, 1997;Kerner, 2000;Schöl et al, 2014), linking estuarine N 2 O production to river eutrophication. Fabisik et al (2023) showed that algae could additionally contribute to N 2 O production. In the Elbe, fresh organic matter from the river with low C/N values as well as high PN and PC contents entered the estuary.…”
Section: Hamburg Port: N 2 O Production In Spring and Summermentioning
confidence: 99%